Magnum, P.I. : The Complete First Season Disc 5 - Gilbert, M. Shilton; John Hillerman; Larry Manetti; Roger E Mosley; Tom Selleck (USA Universal Studios, 1980)
Thomas Magnum is employed on the Hawaiian estate of a wealthy absentee owner name Robin Masters. The estate is run by Jonathan Higgins who mostly tolerates Magnum's presence as head of security on the estate. Magnum is also a private detective whose cases frequently have a humorous overtone and always just enough danger.
The adventures of a Hawaii based private investigator.
Language: English
Subtitle: English
Keywords: Adventure; Crime; Drama; Mystery; Action -- Tv Series